ERP system upgrade: an analysis of the costs, benefits and requirements - Shaw, C. (Cranfield University, 2002)
This project looks at the feasibility of the high performance vehicle manufacturer, Ray Mallock Limited (RML), upgrading their current version of their Frontstep produced Enterprise Resource Planning (ERP) system from version 4 to the latest version 6. The project outlines a cost benefit analysis of the upgrade so RML can see the value of the new features of the system and weigh these up with the costs that would be incurred. The project then goes on to look at the risks that RML would face if they chose to upgrade or not to upgrade the ERP system and the timescales of the upgrade process. Finally, some suggestions are made to ensure that RML can take full advantage of their current system while being in a position to upgrade effectively in the future. After considerable analysis, this report suggests that an upgrade at this point in time for RML is not a viable option due to the high cost and high risk of the project. In addition, this project suggests that that an ERP system needs management and development on an ongoing basis to ensure that a company is in a strong position to take advantage of new versions without having to incur high risks and even higher costs. The ongoing costs of an ERP system are significant and often misjudged by many companies during the implementation phase, especially if they want to stay on the support contracts as they become tied to an upgrade path dictated by the supplier. Companies must also ensure that they are in a position to take advantage of the upgrades and do not lose skills within the business to manage a change of this nature and they have the business and IT infrastructure in place to support the upgrade.